(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes how the mass media effects on the development of Tourism. Integrating tourism with media facilitates to broaden this sector around the economical world. In other words, it will likely bring as a new sector.